Green Flexible Triboelectric Nanogenerators Based on Edible Proteins for Electrophoretic Deposition. (20th November 2022) - Kheirabadi, Noushin Raeisi; Karimzadeh, Fathallah; Enayati, Mohammad Hossein; Kalali, Ehsan Naderi
Abstract: The next generation of wearable electronics for internet of things (IoT) systems, and green energy harvesting require electrically conductive materials with high flexibility, conductivity, and being environmentally friendly. In this study, three biopolymers, cow's milk, soy milk, and egg white liquid, are investigated and compared as spin‐coated positive layers in triboelectric nanogenerators (TENGs). Superior results are obtained using egg white liquid as a novel liquid conductor with comparable conductivity and high transparency. After investigating various disposable polymers as substrates, sandpaper is used to improve the output performance of the proposed egg white liquid based TENG (EW‐TENG). The maximum output power density, voltage, and current of the EW‐TENG are 328.84 mW cm −2, 1720 V, and 16.05 mA, respectively. The fabricated EW‐TENG, with an area of 4 × 4 cm 2, can directly illuminate 55 high‐power blue LEDs and can adequately perform an electrophoretic deposition of ZnO nanoparticles on copper layers without microcracks. The potential distribution of the EW‐TENG obtained by COMSOL Multiphysics software is consistent with the experimental results. Herein, an eco‐environmentally friendly, flexible, and lightweight electronic device for energy harvesting and electrophoretic deposition applications is proposed. Abstract : Eco‐environmentally friendly, sustainable, and low‐cost triboelectric nanogenerators (TENGs) are fabricated using cow's milk, soy milk, and egg white liquid (EW). Among the fabricated TENGs, the EW‐TENG shows ultrahigh output open‐circuit voltage and power density of 1720 V and 328.84 mW cm −2, respectively. Electrophoretic deposition is conducted with the EW‐TENG as a power supply. Coatings obtained are crack‐free with nanoscale particles.